Impact of pre-segmented regions on CT-based evaluation of the Peritoneal Cancer Index: A reader study - Lotte J. S. Fleurkens-Ewals; Marion W. Tops-Welten; Anna F. van Herwijnen; Pieter C. Gort; Cris H. B. Claessens; Ellen S. R. Duijsings; Irene E. G. van Hellemond; Jurgen M. J. Piek; Ignace H. J. T. De Hingh; Max J. Lahaye; Misha D. P. Luyer; Joost Nederend (PLoS ONE, 2026)
Objectives Accurate assessment of peritoneal tumour burden is crucial for treatment selection and prognosis. The Peritoneal Cancer Index (PCI), traditionally assessed by laparoscopy, is increasingly applied to imaging. This study investigates whether pre-segmented radiological PCI (rPCI) regions on CT improve interobserver variability, diagnostic accuracy, and user experience. Materials and methods This prospective, comparative reader study included nine contrast-enhanced CT scans from patients with peritoneal metastases of ovarian, gastric, or colorectal origin. Radiologists, surgeons, and gynaecologists independently scored rPCI on two scans: one with and one without pre-segmented rPCI regions shown as colour overlays. Interobserver variability, mean absolute error compared with surgical PCI (sPCI), and reader confidence were compared between both conditions. User experience was evaluated through structured feedback. Results In total, 82 clinicians from 19 countries participated in this study. Each CT was assessed 8–10 times with and without overlaid segmentations. Pre-segmented region overlays did not significantly improve interobserver variability (p = 0.123), PCI accuracy (mean absolute error, p = 0.374), or reader confidence (p = 0.593). However, with use of segmentations, rPCI values were closer to sPCI in 7 of 9 scans. In regions 9–12, the proportion of participants reporting moderate or high confidence increased from 48–53% without overlays to 59–63% with overlays. User feedback was positive, with 83% of participants reporting the tool as useful, 82% as easy to use, and 71% indicating they would use it in clinical practice. Conclusion Pre-segmented region overlays for CT-based rPCI assessment were positively received by clinicians. Although no statistically significant improvements in interobserver variability or accuracy were observed, the findings of this exploratory study support further evaluation in larger studies to determine their clinical value.